2008
DOI: 10.1186/1471-2334-8-69
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution of hepatitis C virus genotypes in different geographical regions of Pakistan and their possible routes of transmission

Abstract: Background: Information regarding hepatitis C virus genotypes and subtypes circulating in Pakistan and various risk factors for their transmission are not known well. The specific objective of this study was to find out the frequency of various HCV genotypes present in well-characterized Pakistani HCV isolates and their possible routes of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
177
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(214 citation statements)
references
References 37 publications
31
177
6
Order By: Relevance
“…However, when the effect of IFN therapy in patients was analysed, we observed a statistically higher frequency of this allele in SVR patients compared with non-SVR patients. This association is consistent with the observations of Harcourt et al (2001); although they did not report the HCV genotype, it was most probably genotype 1, which is the most prevalent in UK patients in contrast to our study population, which consisted of genotype 3a only, the most common genotype in Pakistan (Idrees & Riazuddin, 2008). These observations are interesting as they indicate a possible mechanism in which the HLA-DQB1*0301 allele is somehow involved in clearance of virus from patients spontaneously by natural immunity or by an IFNsupplemented immune system.…”
Section: Discussionsupporting
confidence: 78%
“…However, when the effect of IFN therapy in patients was analysed, we observed a statistically higher frequency of this allele in SVR patients compared with non-SVR patients. This association is consistent with the observations of Harcourt et al (2001); although they did not report the HCV genotype, it was most probably genotype 1, which is the most prevalent in UK patients in contrast to our study population, which consisted of genotype 3a only, the most common genotype in Pakistan (Idrees & Riazuddin, 2008). These observations are interesting as they indicate a possible mechanism in which the HLA-DQB1*0301 allele is somehow involved in clearance of virus from patients spontaneously by natural immunity or by an IFNsupplemented immune system.…”
Section: Discussionsupporting
confidence: 78%
“…In 2004, a panel of 30 top gastroenterologists of the country met at a conference and reported that 75%-90% of HCV patients in Pakistan had genotype 3a [8] . Qazi et al [92] reported in 2006 that 71% [95] .…”
Section: Genotypesmentioning
confidence: 99%
“…Hakim et al [18] reported in 2008 that 51% of HCV patients had genotype 3a; 24% had 3a/3b co-infection and 16% had genotype 3b, while similar results were also reported by Afridi et al [94] who stated that 50% of HCV patients had genotype 3a followed by 3b and 1a. The most detailed study was conducted by Idrees and Riazuddin in 2008, who performed genotyping of 3351 patients and reported that genotype 3a was the most prevalent genotype in Pakistan; their results are summarized in Figure 1 [95] .…”
Section: Genotypesmentioning
confidence: 99%
“…The patients were stratified according to age, sex and grade of liver fibrosis according to METAVIR scoring system. 3 second group(31-50 years) had a mean age of 40.24(±5.2 SD) and had a 29 patients and last group(51-70) had a mean age of 58.08(±5.05 SD) and had a total of 13 patients. The patients were also divided on the basis of being diabetic or non-diabetic.…”
Section: Resultsmentioning
confidence: 99%